Two new species of Roquettea Mello-Leitão, 1931 from northern Brazil (Opiliones: Laniatores: Cosmetidae) - Kury, Adriano B.; Ferreira, Cláudio P. (Zootaxa, 2012)
Two new species of the genus Roquettea Mello-Leitão, 1931 (Opiliones: Cosmetidae) are described from Pará State,northern Brazil. Roquettea carajas sp. nov. has two broad swellings on mesotergal area I of male and Roquettea peba sp.nov. has a wide and high eye mound with globoid eyeballs and the closest structure to a chelate pedipalpus in Laniatoresso far described. Both species have greatly thickened conic apophyses on mesotergal area III. A key is given to the (now)6 species of Roquettea. The described diversity of genus Roquettea increased from only one species to six in only a few years, mostly known from only a few specimens, suggesting a high degree of undersampling of those rare cosmetids.